The interplay among sleep patterns, social habits, and environmental cues: insights from the Spanish population and implications for aligning daily rhythms - Bonmatí-Carrión, María-Ángeles; Vicente-Martínez, Jesús; Madrid, Juan Antonio; Rol, Maria Angeles (Frontiers in Physiology, 2024)
The interplay among sleep patterns, social habits and environmental cues is becoming increasingly more important for public health and well-being due to its connection to circadian desynchronization. This paper explores said connections in Spain (official and solar time mismatched), introducing the "Three Times Score"‒based on questions widely used in the field‒ for exploring the interplay of daily rhythms. The questionnaire covers sleep-related habits, social time, and environmental time. The study includes 9,947participants (34.89±12.15y/o; 5,561women) from different Spanish regions. Sleep parameters were obtained for work and free days, and a modified version of the sleep-corrected midsleep on free days (MBFbc) and a parameter similar to social jet lag, both derived from bed-time. A number of indexes were computed to compare bed, work-related habits, and natural light/dark cycle. Mixed-effect regression was used to test biological, social and environmental factors influence on sleep-related parameters: bedtime, wake-up time, time in bed and mid-bedtime. Waking-up occurred 2hours earlier on work days (7:10±0:01) than on free days (9:15±0:01). Bed times were 1hour earlier on work days (23:46±0:01) than on free days (00:45±0:01), whereas time in bed was over 1 hour shorter on work (7h 23min) versus free (8 hours 29 minutes) days. Women went to bed earlier and woke up later, spending more time in bed. Differences in sleep habits were observed between work and free days across all ages. Younger adults reported going to bed later than older and younger groups, especially on free days. Adolescents and young adults also woke-up later than other age groups, especially on free days. Social jet lag (relative to bed) and desynchronization also varied with age, with younger adults exhibiting higher levels. According to the multiple regression analysis, social (day type, work start time, alarm clock), biological (age, sex) and environmental (sunset) factors significantly contribute to predicting sleep/bed related schedules. This study provides insights into sleep habits in the Spanish population, introducing the Three Times Score as a complementary tool for exploring the interactions between sleep/bed-related habits, natural darkness and work-related schedules. Understanding this interplay is crucial for developing tailored interventions to improve sleep and well-being.